When you were here - Whitney, Daisy. (Little, Brown and Company, 2013)
When his mother dies three weeks before his high school graduation, Danny goes to Tokyo, where his mother had been going for cancer treatments, to learn about the city his mother loved and, with the help of his friends, come to terms with her death.